Reading identities: a case study of grade 8 learners' interactions in a reading club - Scheckle, Eileen Margaret Agnes (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2015)
This study offers an account of reading clubs as a literacy intervention in a grade 8 English class at a former 'Coloured' high school in South Africa. Using Margaret Archer's social realist methodology, it examines different practices of 'reading' used by learners in talking and writing about text. Archer's analytical dualism and morphogenetic model provided an explanatory framework for this study. Analytical dualism allows for the separation of the parts (structural and cultural elements) from the people (the grade 8 learners) so as to analyse the interplay between structure and culture. The morphogenetic model recognises that antecedent structures predate this, and any study but that through the exercise of agency, morphogenesis, in the form of structural elaboration or morphostasis in the form of continuity, may occur. This study used a New Literacies perspective based on an ideological model of literacy which recognises many different literacies, in addition to dominant school literacies. Learners' talk about books as well as personal journal writing provided an insight into what cultural mechanisms and powers children bring to the reading of novels. Understandings of discourses as well as of Gee's (1990; 2008) construct of Discourse provided a framework for examining learners' identities and shifts as readers. The data in this study, which is presented through a series of vignettes, found that grade 8 learners use many different experiences and draw on different discourses when making sense of texts. Through the separation of the structural and cultural components, this research could explore how reading clubs as structures enabled learners to access different discourses from the domain of culture. Through the process and engagement in the reading clubs, following Gee (2000b), learners were attributed affinity, discoursal and institutional identities as readers. It was found, in the course of the study, that providing a safe space, scaffolding, multiple opportunities to practice and a variety of reading material, helped learners to access and appropriate dominant literacies. In addition, learners need a repertoire of literacy practices to draw from as successful reading needs flexibility and adaptability. Reading and writing inform each other and through gradual induction into literary writing, learners began to appropriate and approximate dominant literacy practices. Following others who have contributed to the field of New Literacy Studies (Heath, 1983; Street, 1984; Gee 1990; Prinsloo & Breier, 1996), this study would suggest that literacies of traditionally underserved communities should not be considered in deficit terms. Instead these need to be understood as resources for negotiating meaning making and as tools or mechanisms to access dominant discourse practices. In addition the resilience and competition from Discourses of popular culture need to be recognised and developed as tools to access school literacies.
Keywords: Group reading -- South Africa; Reading (Middle school) -- South Africa; Literacy programs -- South Africa; Identity (Psychology) in adolescence; Identity (Psychology) in adolescence -- South Africa; Discourse analysis -- Social aspects; Critical realism